2010
DOI: 10.1123/ijsnem.20.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Intake in National-Level Sri Lankan Athletes

Abstract: Intake of dietary supplements is widespread among athletes in developed countries. This study evaluated the use of dietary supplements in athletes from a developing country. Dietary supplementation practices of 113 national-level athletes age 15-35 yr in Sri Lanka were assessed. All athletes from track-and-field, badminton, football, swimming, cycling, and karate squads who consented to participate in the study were administered an anonymous questionnaire by an interviewer. Information on number of supplements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
4
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 17 publications
8
45
4
12
Order By: Relevance
“…The results obtained in present study differ from many others that have found that vitamins, minerals, and/or multivitamin/minerals were the most frequently consumed supplements among athletes [2, 5,6,8,17]. Although 17.5% and 23.3% of the athletes investigated consumed minerals and vitamins, respectively, these supplements were not included in the list of the four most frequently used supplements.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The results obtained in present study differ from many others that have found that vitamins, minerals, and/or multivitamin/minerals were the most frequently consumed supplements among athletes [2, 5,6,8,17]. Although 17.5% and 23.3% of the athletes investigated consumed minerals and vitamins, respectively, these supplements were not included in the list of the four most frequently used supplements.…”
Section: Discussioncontrasting
confidence: 54%
“…The most frequently mentioned reasons given by athletes for the use of dietary supplements include increase in energy and strength, improvement in performance, maintenance or enhancement of overall health and the immune system, prevention of nutritional deficiencies, and also to speed injury recovery [4][5][6][7]. Aiming at obtaining these results, the most commonly consumed dietary supplements by this population are sports drinks, multivitamins and minerals, proteins, and amino acids [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most prevalent sport was intermittent sports (40.3%); this result contradicts previous studies, in which intermittent sports presented the least consumption of supplements (12,16). This difference may be due to the grouping of modalities as well as contradictory definitions of dietary supplements.…”
Section: Discussioncontrasting
confidence: 56%
“…The decision to use these products is not always rational (8) and may be influenced by intrinsic and extrinsic factors, such as age (12), sex (13)(14)(15), type of sport (13,14), training volume (13,14,16), performance level (14), motivation (13,17), an athlete's knowledge on supplementation and the constant charges of coaches, sponsors and media for better results (18,19).…”
Section: Introductionmentioning
confidence: 99%